131k views
2 votes
The solutions of the quadratic equation 0 = (x + 3)(x - 2)

are
0 -6 and 0.
04 and 3.
0-3 and 2
0 -2 and 1.

User Arashdn
by
5.2k points

1 Answer

2 votes

Answer:

x = -3 or x = 2

Explanation:

It is given a quadratic equation,

(x + 3)(x - 2) = 0

To find the solution of given equation

Let (x + 3)(x - 2) 0

⇒ either (x + 3) = 0 or (x - 2) = 0

If (x + 3) = 0 then x = -3

If (x - 2) = 0 then x = 2

Therefore the solution of given equation are

x = -3 or x = 2

User Gaynorvader
by
4.7k points